Compositionally tuned NixSn alloys as anode materials for lithium-ion and sodium-ion batteries with a high pseudocapacitive contribution. (1st May 2019) - Li, Junshan; Xu, Xijun; Luo, Zhishan; Zhang, Chaoqi; Yu, Xiaoting; Zuo, Yong; Zhang, Ting; Tang, Pengyi; Arbiol, Jordi; Llorca, Jordi; Liu, Jun; Cabot, Andreu
Abstract: Nickel tin alloy nanoparticles (NPs) with tuned composition Nix Sn (0.6 ≤ x ≤ 1.9) were synthesized by a solution-based procedure and used as anode materials for Li-ion batteries (LIBs) and Na-ion batteries (SIBs). Among the compositions tested, Ni0.9 Sn-based electrodes exhibited the best performance in both LIBs and SIBs. As LIB anodes, Ni0.9 Sn-based electrodes delivered charge-discharge capacities of 980 mAh g −1 after 340 cycles at 0.2 A g −1 rate, which surpassed their maximum theoretical capacity considering that only Sn is lithiated. A kinetic characterization of the charge-discharge process demonstrated the electrode performance to be aided by a significant pseudocapacitive contribution that compensated for the loss of energy storage capacity associated to the solid-electrolyte interphase formation. This significant pseudocapacitive contribution, which not only translated into higher capacities but also longer durability, was associated to the small size of the crystal domains and the proper electrode composition. The performance of Nix Sn-based electrodes toward Na-ion storage was also characterized, reaching significant capacities above 200 mAh g −1 at 0.1 A g −1 but with a relatively fast fade over 120 continuous cycles. A relatively larger pseudocapacitive contribution was obtained in Nix Sn-based electrodes for SIBs when compared with LIBs, consistently with the lower contribution of the Na ion diffusion associated to its larger size. Graphical abstract: Pseudocapacitive contribution comparison between LiBs and SiBs.Image 1